Odraz medjezikovnih stikov v prekmurskem besedju - Koletnik, Mihaela (Slavia Centralis, 2020)
Reflection of Inter-lingual Interlacing in Upper Mura Texts In the article the author focuses on Prekmurian vocabulary related to pottery and agricultural activities. The terminology for pottery and agricultural activities discussed in the article is disappearing from the active vocabulary of speakers, owing to the changed way of life. Prekmurian expressions describing pottery and agricultural fields and other issues of peasant life still constitute a rich part of the original Slavic substratum. However, the old Slavic terminology is rapidly vanishing among the middle generation of speakers, while the younger generation is not familiar with it at all. Terms of foreign origin in dialectal pottery and agricultural terminology are mostly German and Romance borrowings.